HUBUNGAN KARAKTERISTIK, RIWAYAT KELUARGA DAN PENGETAHUAN PADA IBU YANG MENDERITA KANKER SERVIKS DALAM KETERLAMBATAN MENCARI PENGOBATAN KEPELAYANAN KESEHATAN - Elisabeth surbakti; Susi Adranelly Simare-mare; Arihta Sembiring (Poltekkes Kemenkes Medan, 2020)
Introduction: Cervical cancer is cancer that occurs in the cervix of the uterus, is the entrance to the uterus located between the uterus and the vagina. Mothers with cervical cancer 65.5% come to health care already in an advanced stage, where this will have an impact on economic, social, physical, psychological suffering and even increased mortality due to cervical cancer. This study aims to determine the relationship of characteristics, family history of mothers suffering from cancer and maternal knowledge about cervical cancer in delay in seeking treatment at the RSUH. Adam Malik Medan. Methods: This study used a cross-sectional study design. The population in this study were all women with cervical cancer who had been diagnosed through histopathological examination from Stage Ia to Stage IVb who were treated in the Midwifery and Midwifery Oncology Hospital of Adam Malik General Hospital Medan. The way to take sample is by using non probability sampling. Research / Discussion Results: Based on univariate analysis that the delay of respondents in seeking treatment for health services in patients with cervical cancer, generally has an advanced stage (67.5%). Characteristics of respondents; age> 40 years (58%), low education (34.3%), having more than 2 children (77.5%), low socioeconomic (37.3%), having a family with a history of cancer (39.1%). Based on univariate analysis states that: There is a significant relationship: age> 40 years, low education, having more than 2 children, low socioeconomic, poor knowledge, family history of cancer where p <0.05 with 95% CI, to delays seek treatment to health services. Conclusion: increasing maternal awareness through IEC with early detection of IVA or pap smears, increasing knowledge can prevent delays in patients coming to health care. Respondents who have a family history of cancer or not have the potential for cervical cancer, so they still need to be routinely detected early. Optimize efforts to prevent cervical cancer, by raising awareness of the awareness and importance of cervical cancer screening through early detection of either IVA or pap smear tests, health promotion so that people do not come at an advanced stage to health services.